2024
DOI: 10.1186/s12934-024-02345-w
|View full text |Cite
|
Sign up to set email alerts
|

The strain-dependent cytostatic activity of Lactococcus lactis on CRC cell lines is mediated through the release of arginine deiminase

Rafał Jastrząb,
Rafał Tomecki,
Aneta Jurkiewicz
et al.

Abstract: Background Colorectal cancer (CRC) is one of the most commonly diagnosed cancers, posing a serious public health challenge that necessitates the development of new therapeutics, therapies, and prevention methods. Among the various therapeutic approaches, interventions involving lactic acid bacteria (LAB) as probiotics and postbiotics have emerged as promising candidates for treating and preventing CRC. While human-isolated LAB strains are considered highly favorable, those sourced from environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 137 publications
0
1
0
Order By: Relevance
“…Recently, one study demonstrated the antiproliferative activity of Lactococcus lactis strain Lc4 on CRC cell lines via the release of arginine deiminase (ADI), a cytostatic agent [216].…”
Section: Microbiota As a Therapeutic Targetmentioning
confidence: 99%
“…Recently, one study demonstrated the antiproliferative activity of Lactococcus lactis strain Lc4 on CRC cell lines via the release of arginine deiminase (ADI), a cytostatic agent [216].…”
Section: Microbiota As a Therapeutic Targetmentioning
confidence: 99%